2019
DOI: 10.1186/s12875-018-0881-8
|View full text |Cite
|
Sign up to set email alerts
|

Helpful ways providers can communicate about persistent medically unexplained physical symptoms

Abstract: BackgroundCommunication between patients and providers about persistent “medically unexplained” physical symptoms (MUS) is characterized by discordance. While the difficulties are well documented, few studies have examined effective communication. We sought to determine what veterans with Gulf War Illness (GWI) perceive as the most helpful communication from their providers. Veterans with GWI, a type of MUS, have historically had complex relationships with medical providers. Determining effective communication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…Symptoms, by definition, are patients’ own experiences as opposed to externally “objective” measures of disease and have thus far been the only consistent marker of GWI in affected veterans. For many years, the lack of diagnosable abnormalities on physical exam and routine clinical lab tests commonly led to provider assumptions that nothing was wrong with veterans who reported chronic GWI symptoms, or that their health problems were the result of deployment stress and/or psychiatric in nature [ 48 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms, by definition, are patients’ own experiences as opposed to externally “objective” measures of disease and have thus far been the only consistent marker of GWI in affected veterans. For many years, the lack of diagnosable abnormalities on physical exam and routine clinical lab tests commonly led to provider assumptions that nothing was wrong with veterans who reported chronic GWI symptoms, or that their health problems were the result of deployment stress and/or psychiatric in nature [ 48 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Instead, they often receive excessive healthcare [ 19 ], overly focused on diagnostic tests to determine the cause of the MUS [ 20 ]. Studies have found that individuals prefer explicit diagnoses such as chronic fatigue syndrome over the uncertainty of no diagnosis [ 53 ], and that they find acknowledgement and validation to be the most helpful communication from their provider [ 31 ]. How diagnosis for a MUS condition would influence Veterans’ care is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were enrolled in a larger ( N = 268) interventional study examining the effectiveness of Problem-Solving Treatment to reduce disability for Veterans with Gulf War Illness [ 31 , 35 37 ]. To be eligible for the study, Veterans had to 1) deploy to Operation Desert Storm or Operation Desert Shield between August 1990 and November 1991, 2) meet the case definition for Gulf War Illness [ 2 ], and 3) report disability on the World Health Organization Disability Assessment Schedule (WHODAS 2.0) [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings indicate an urgent need for improving knowledge of French medical specialists on bodily distress, and offering them trainings aimed at changing their representations of attitudes toward patients with persistent "unexplained" somatic symptoms. 9,10…”
Section: Statistical Analysis Was Based On Multiple Correspondencementioning
confidence: 99%